2016
DOI: 10.1007/s13277-016-5309-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial HSP70 peptide epitope 407–426 as adjuvant in tumor-derived autophagosome vaccine therapy of mouse lung cancer

Abstract: Tumor-derived autophagome (DRibble) is an effective therapeutic cancer vaccine inducing T cell recognition and death of tumor cells in mice. However, the potential for improved anti-tumor response still remains. Our previous study demonstrated that two repeats of a mycobacterial HSP70 (M2) peptide acted as adjuvant in improving anti-tumor efficacy of human umbilical vein endothelial cell (HUVEC) vaccine. Here, a DRibble vaccine conjugated with M2 (DRibble-M2) was designed as a novel vaccine to enhance anti-tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Previous studies using mouse models have shown that HSP70 can be used as an adjuvant in cancer vaccine development strategies [45,46]. HSPs have therefore been harnessed as adjuvants of vaccines against cancers and infectious diseases [47]: examples include Phase I clinical trials for Glioblastoma (HSP70), colon carcinoma, Phase I-II studies for Non-small cell lung carcinoma (HSP70-activated NK cells) and a Phase I HIV vaccine study [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using mouse models have shown that HSP70 can be used as an adjuvant in cancer vaccine development strategies [45,46]. HSPs have therefore been harnessed as adjuvants of vaccines against cancers and infectious diseases [47]: examples include Phase I clinical trials for Glioblastoma (HSP70), colon carcinoma, Phase I-II studies for Non-small cell lung carcinoma (HSP70-activated NK cells) and a Phase I HIV vaccine study [25].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion diphtheria toxin (DT) and two tandem repeats of HSP70 407-426 with TCLs elicit strong humoral and cellular immune responses, leading to the growth inhibition of breast cancer (178). In addition, a tumor-derived autophagosome (Dribble) vaccine conjugated with HSP70 407-426 significantly induced a higher expression of antigen-specific cytotoxic T lymphocytes (CTLs) (179). Genetic vaccines encompass DNA or RNA vaccines delivered by viruses or plasmids.…”
Section: Developing Hsp70-based Vaccinesmentioning
confidence: 99%
“…Some HSP70-based vaccines were designed to enhance the antigen-presenting capacity of DCs to T cells based on the results that HSP70 promoted DCs maturation, upregulation of co-stimulatory molecule, and cytokine secretion via interacting with DCs [ 184 ]. These vaccines that have been preliminarily proven effective in animal experiments include a tumor-derived autophagome (Dribble) vaccine conjugated with mycobacterial HSP70407–426 (M2) peptide, soluble form of B, and T lymphocyte attenuator (sBTLA) in combination with HSP70 vaccine where recombinant adeno-associated viral (AAV) vectors served as the gene delivery, DCs pulsed with recombinant fusion protein of CEA 576–669 and HSP70-like protein 1 (HSP70L1), and DCs pulsed with tumor cell lysate which was pulsed with M2 peptide and OK-432 [ 185 , 186 , 187 , 188 , 189 ].…”
Section: Targeting Hsp70 In Cancer Therapymentioning
confidence: 99%